산업체 위탁생의 계속교육에 관한 만족도 - 김진수; Jin Soo Kim; 장희경; Hee Gyung Jang (Han'guk Ch'iwisaeng Hakhoe chi, 2013)
Objectives : The purpose of this study was to evaluate the relationship between smoking and peridontal diseases in Korean adults based on the data from the Korea National Health and Nutrition Examination Survey 2010. Methods : This study was carried out from May 15 to June 15, 2012, 200 college students working in companies in Chungnam, Korea participated in the study. Results : 1. Both study and work were distress to male and female students with a statistically significant difference (p<.05). 2. Major subjects satisfied male and female students (p<.05). 3. There was a significant differences between gender specific satisfaction. (p<.05). 4. Students were satisfied with college education (p<.05). 5. The companies tried to understand the students` difficulty in studying (p<.05).group. Conclusions : It is very important to establish the practice and theory in college students working in companies.